Genetic diversity of agro-morphological traits and blast disease reaction in elite rice genotypes for hybrid breeding (Bangladesh Rice Journal, 2026)
Global rice production faces enormous challenges from climate-induced abiotic and biotic stresses, with rice blast disease caused by the fungus Pyricularia oryzae posing a major threat to yield and food security. Developing and deploying rice cultivars with resistance to blast disease remains the most effective and sustainable approach to mitigate this constraint. To identify potential sources of resistance, a study was conducted during 2022–2023 focusing on the development of hybrid rice parental lines. Out of 43 genotypes evaluated, 18 exhibited resistance to a virulent blast isolate, while the remaining 25 showed susceptible reactions. Agro-morphological traits such as plant height, panicle length, days to maturity, number of effective tillers, total spikelets per panicle, filled grains per panicle, spikelet fertility percentage, grain yield per hill, and notably the blast disease severity score, were key contributors to phenotypic variability among these genotypes. Based on these traits, the genotypes were categorized into five distinct clusters. Principal component analysis revealed that the first three components explained 67.45% of the total variation. Genotypes G22 (IR126055-46-3-2-B), G13 (BHR362- 8-6-5-26-9), G11 (BHR360- 86-41-7-26-1), and G10 (BHR359-11-30-7-2) from cluster III exhibited high yield potential, whereas genotypes G42 (IR127278-114-3-3-2), G38 (BHR383-53-8-13-1-1), and G43 (BR9390-6-2-2-1) from cluster IV showed notable blast resistance, underscoring their value for hybrid rice development programs. To employ these traits, genotypes from the aforementioned clusters could be made testcross with promising CMS (Cytoplasmic Male Sterile) lines that would offer a good scope to explore the source of high yielding and blast resistance elite restorer or maintainer lines. These findings offer valuable insights for rice breeders aiming to develop high yielding and blast-resistant hybrid varieties tailored to the agro-ecological conditions of Bangladesh.Bangladesh Rice J.28(1): 41-56